Revisiting the cognitive and behavioral aspects of loneliness: Insights from different measurement approaches - Andrej Skoko; Noëmi Seewer; Marcus Mund; Tobias Krieger (PLoS ONE, 2025)
Loneliness is increasingly recognized as a critical public health issue that profoundly affects psychological well-being and social functioning. This study evaluates cognitive and behavioral differences associated with different facets of loneliness. We classified 790 German-speaking adults (MAge = 31.86 (12.48), 81% female) as lonely or not lonely based on three dimensions - loneliness frequency, distress, and chronicity - and tested for group differences regarding cognitive and behavioral aspects, as proposed by the cognitive model of loneliness, while controlling for depressive and social anxiety symptoms. The results indicate fair to substantial agreement between the three classification methods. Further, we found significant group differences regarding all components, such as interpretation bias, social avoidance, and self-esteem, with each loneliness classification method. Our findings highlight the multifaceted nature of loneliness and underscore the importance of applying diverse methods to fully capture its complexity. This study contributes to a more nuanced understanding of loneliness and its implications, suggesting that interventions should consider the specific dimensions of loneliness to effectively address its cognitive and behavioral ramifications.